“Cognitive Linguistics: An Approach to the Study of Language and Thought” (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article establishes the focus on Cognitive Linguistics as a framework to understand the intricate relationship between language and human cognition. Cognitive Linguistics stands at the intersection of language, cognition, and the mind, offering a unique lens through which scholars unravel the intricate relationship between language and human thought processes. Introduction sets the stage by emphasizing the interdisciplinary nature of Cognitive Linguistics in exploring the connection between language and cognition. Introduces the core concept of Cognitive Linguistics, departing from traditional structural approaches and emphasizing the role of cognitive processes in language. At its core, Cognitive Linguistics diverges from traditional structural approaches by emphasizing the role of cognitive processes in language comprehension, production, and conceptualization.